Personal Health and Consumer Informatics - Guardia, A.; Boyer, B. C.; Section Editors for the IMIA Yearbook Sections on Personal Health Informatics and on Consumer Informatics (Yearbook of Medical Informatics, 2012)
To summarize current outstanding research in the field of Personal Health and Consumers Informatics.A selection of excellent research articles published in 2011 in the field of Personal Health Informatics and Consumer Informatics.This selection of articles shows that Personal Health Informatics is changing. Indeed, the different solutions tended to the doctors and their interaction, but also tended to the patient in order for him to be more active in his own medical healthcare. The consumer section highlights the development of the social network and the possible limitations.
Keywords: Personal health informatics; consumer informatics; personal heatlh record; smartphone; social networks